2011
DOI: 10.1152/ajpheart.01222.2010
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in physiological cardiac hypertrophy are associated with exercise-mediated changes in energy substrate availability

Abstract: Exercise-induced cardiac hypertrophy has been recently identified to be regulated in a sex-specific manner. In parallel, women exhibit enhanced exercise-mediated lipolysis compared with men, which might be linked to cardiac responses. The aim of the present study was to assess if previously reported sex-dependent differences in the cardiac hypertrophic response during exercise are associated with differences in cardiac energy substrate availability/utilization. Female and male C57BL/6J mice were challenged wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 37 publications
7
60
1
1
Order By: Relevance
“…This would provide a means of alternative disposal in glucose adipose tissue rather than liver. Sex differences in phenotypic outcomes of Irs2 (Masaki et al 2004) and PPARg knockout (Duan et al 2010;Kadowaki et al 2007) and Akt1 activation (Foryst-Ludwig et al 2011;Chen et al 2013) have been reported previously.…”
Section: A B C D E Fsupporting
confidence: 64%
“…This would provide a means of alternative disposal in glucose adipose tissue rather than liver. Sex differences in phenotypic outcomes of Irs2 (Masaki et al 2004) and PPARg knockout (Duan et al 2010;Kadowaki et al 2007) and Akt1 activation (Foryst-Ludwig et al 2011;Chen et al 2013) have been reported previously.…”
Section: A B C D E Fsupporting
confidence: 64%
“…This would, however, be consistent with animal models demonstrating that females have higher LV hypertrophic response to exercise compare to males when compared for quantity of exercise. 24 With regards to our secondary objectives, the small differences in LVEF or LVGLS did not translate in meaningful differences in stroke volume index or the more load independent metrics of ventricular function such as LV strain rate. 25 With regards to atrial function metrics, our study also suggests absence of meaningful sex related differences.…”
Section: Discussionmentioning
confidence: 93%
“…5 We demonstrated recently that female hearts after chronic exercise with forced treadmill running showed augmented Akt phosphorylation compared with male hearts, indicating activation of this pathway. 6 Taken together, it appears that female hearts have a stronger capability to adapt to a protective exercise-induced MH phenotype.…”
Section: Studies In Rodentsmentioning
confidence: 99%
“…5,6 The underlying molecular mechanisms of these sex differences in exerciseinduced MH are multifactorial. Konhilas et al 5 investigated multiple signaling molecules involved in the development of MH including enhanced proportional increase of Ca 2+ /calmodulin-dependent kinase (CaMK) activity in trained female hearts compared with males and a persistent phosphorylation of glycogen synthase kinase 3 beta (GSK-3β).…”
Section: Studies In Rodentsmentioning
confidence: 99%
See 1 more Smart Citation